(untitled) (Repertorio Científico, 2023)
This paper reports on the didactic and disciplinary knowledge of a collective of elementary school teachers when faced with solving a task in the field of statistics of the second cycle of the study programs of the Ministry of Public Education of Costa Rica. The research was based on the cognitive, mediational, ecological, epistemic, interactional, and emotional facets of the didactic suitability of the Ontosemiotic Approach. It followed an exploratory and mixed approach, through the analysis of the responses given by 17 teachers from public and private schools. The results show that the teachers did not manage to mobilize or identify the knowledge, skills, and characteristics they should bring into play to provide a correct solution to the situation posed. The need for a specific qualification framework to guide the minimum mathematical knowledge required in the initial training of teachers of I and II cycle of General Basic Education is evident.